Perceived Impact of the Activities of Unknown Gun Men (UGM) on the Growth and Profitability of Large, Medium, Small and Micro, Businesses in Onitsha Main Market, Anambra State - Ilodigwe, Anthonia Onyinye; Uzor, Bonaventure Chigozie (Social Science Research, 2024)
The activities and attacks of unknown gunmen is arguably a relatively recent phenomenon especially in south-eastern states of Nigeria that had instilled fear in the minds of people as a result of their deadly and destructive activities which has led to recent disruption in business activities especially the sit-at-home order. Thus, this paper attempts to investigate the perceived impact of the activities of Unknown Gun Men (UGM) on the growth and profitability of Large, Medium, Small and Micro, businesses in Onitsha main market. The relative deprivation theory formed the theoretical framework of the study and the mixed methods research design was adopted by the researcher. A sample size of 204 participants was drawn Onitsha main market, Anambra state for the collection of quantitative data whereas 4 persons were engaged in In-Depth Interview sessions. The quantitative data collated from the field were analyzed using descriptive statistics such as frequency counts and percentages while thematic analysis was used in analysing the qualitative data. The study found that UGM activities have negative impact on the growth of businesses in Onitsha main market as UGM attacks scare away investors, lead to destruction of business premises/properties and discourages business expansion by existing business owners. The study also found that the activities of UGM lead to decrease in profit of Large, medium, small and micro businesses in Onitsha main market as a result of reduction in business days due to sit-at-home orders. The study recommended among others granting of the sovereign state of the Republic of Biafra by the Nigerian government will contribute greatly in curbing the activities of UGM since it the major agitation of those involved in UGM attacks.